Las tecnologías de la información y comunicación y su aplicación en el proceso de enseñanza-aprendizaje en los estudiantes del tercer año de bachillerato de la Unidad Educativa Quevedo del Cantón Quevedo, Provincia de los Ríos, periodo 2015 – 2016 - Rosario Quiñonez, Blanca Aurora (2015)
This research allows to know the importance of information and communication technology; the use of these tools help to improve the learning of students in the third year of high school in the educational unit "Quevedo" Quevedo Canton, Province of the Rivers; It is very common to hear today on the imminent need to incorporate ICTs into the educational system in general, taking into account the degree of influence they have achieved in everyday life of the average citizen and use almost daily and normal, according Studies in Ecuador by some schools show that there is still little use of ICT in teaching within the teaching-learning process, which significantly affects the development of the various educational activities, such as unit educational Quevedo, whose inquiry reflected the need to implement new technological equipment to improve teaching strategies used by the teacher to ensure uptake of the given information and raise awareness of students, as the appropriate use of information and communication technology can function in everyday life always being informed of the events in the world